Information support for the procedure of power consumption planning in the municipal water supply system - Davydenko, Nina; Davydenko, Volodymyr; Davydenko, Liudmyla (Моделювання, керування та інформаційні технології, 2019)
The article deals with the issue of determining the energy baseline of municipal water supply facilities, taking into consideration their actual operation conditions. The purpose of the article is to develop the principles of organization of information support for the procedures of power consumption planning and their integration into the energy management system. The formalization of the power consumption planning process has been performed based on the object-oriented technology. Classes that take into account the characteristics of the facility, water consumption, methods of planning water supply and power consumption have been formed. Description of the properties and methods of the classes has been accomplished. The architecture of the information support system for planning procedures has been proposed. WEB-oriented technologies has been suggested to use for information exchange. This allows creating a single information space, taking into consideration the actual operation conditions of the research object.